(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
There is no denial in the fact that pen can bring revolutionary changes for anyone who knows how to use it, literature was very lately used by the dalit writers to raise their voice and to show their presence in the literary sphere. Literature, apart from many other things, has always been used by writers as arsenal against the established socio-political norms, long drawn out traditions, dull and dreary customs and hypocrisy. There has always been element of protest in the literature which is shaped on the basis of the assumption that there exists a close interaction and relationship between politics and creative expressions. Indeed this protest symbolizes the changing attitudes to sociopolitical situations, priorities and concerns of writers with changing times from the past to present. (Singh 187)